2019
DOI: 10.1002/eco.2113
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological impacts of afforestation in the semiarid Patagonia: A modelling approach

Abstract: Afforestation has been widely encouraged with different goals, including as a strategy to tackle global warming. However, the side-effects of this land-use transformation have been in many cases underestimated. Particularly, the hydrological impacts may become relevant in (semi)arid regions where water is a key element. In this work, we evaluated the hydrological effects triggered by afforestation with ponderosa pine in the semiarid Argentine Patagonia that is currently a focus of afforestation programs. For t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…For instance, interception rates of up to four times higher have been measured in dry forests of the region compared with pastures (Magliano et al, 2016). Likewise, the deeper root system would have allowed the dry forest to sustain higher ET rates than the pasture during drought, pattern already observed in grassland areas that were afforested (Milkovic et al, 2019; Nosetto, Jobbágy, Brizuela, & Jackson, 2012).…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…For instance, interception rates of up to four times higher have been measured in dry forests of the region compared with pastures (Magliano et al, 2016). Likewise, the deeper root system would have allowed the dry forest to sustain higher ET rates than the pasture during drought, pattern already observed in grassland areas that were afforested (Milkovic et al, 2019; Nosetto, Jobbágy, Brizuela, & Jackson, 2012).…”
Section: Resultsmentioning
confidence: 68%
“…The NDVI and EVI are suitable indexes to assess the condition of the ecosystem, given their connection with primary productivity and green biomass (e.g., Goward & Dye, 1987; Sims et al, 2006). Likewise, Ts is closely associated with the heat exchange of vegetation canopies with the surrounding atmosphere and particularly with evapotranspiration (e.g., Milkovic, Paruelo, & Nosetto, 2019; Rotenberg & Yakir, 2010). For NDVI and EVI, we used the MOD13Q1 product and for Ts we used the MYD11A2 product.…”
Section: Methodsmentioning
confidence: 99%
“…Forests and trees are important modulators of global, regional, and local hydrological cycles and patterns [22,59,60]. Negative hydrological impacts, such as the depletion of soil water and reduced annual runoff and water yields, are often observed for dryland afforestation [18,20,24], especially in large-scale planting schemes [19,61]. However, with the excessive cropland irrigation in Khorezm [5]), the reduction in all examined water balance components following the afforestation of marginal land reflects the reduced irrigation inputs and lowered drainage output.…”
Section: Impact Of Afforestation On Irrigation Water Savings and Drainagementioning
confidence: 99%
“…Although these results may discourage conservation, Galleguillos et al (2021) reported that conservative scenarios focused on native forest protection and restoration could partially mitigate the effect of climate change in Mediterranean basins. Future efforts should focus on understanding the hydrological role of different vegetation cover (e.g., Milkovic et al, 2019), under changing climatic conditions in northwestern Patagonia.…”
Section: Synergistic Hydrological Effects Between Climate and Lccmentioning
confidence: 99%